Beyond achievement goals: How different goals drive second language learning and achievement - Li, Jiajing; Mendoza, Norman B.; King, Ronnel B. (Studies in Second Language Learning and Teaching, 2025)
Goals are central to understanding how students learn a second language. Much of the existing research on goals in the field of language learning has focused exclusively on achievement goals, particularly mastery and performance goals. However, exclusively focusing on achievement goals precludes language researchers from exploring other important types of goals such as work avoidance, social, and personal best goals. Furthermore, other key theoretical perspectives, such as goal content, goal-setting, and goal-complex approaches, are neglected in second language learning research. Hence, the paper aims to: (1) introduce second language researchers to other goal perspectives that might be useful to understanding language learning, such as achievement goal, goal content, goal-setting, and goal complex approaches, (2) provide theoretical insights into how different goal theories can advance language learning research and (3) offer practical implications for language researchers and teachers on how to harness goal-related insights, ideas, and models to improve students’ language learning.